Scorched-Earth as Defensive Signaling in Bengkulu, 1945–1949: A Microhistorical Process-Tracing Study - Alvido Praja; Siwi Ponika; Rahmad Hidayatullah (JPI: Jurnal Pustaka Indonesia, 2024)
This study reconstructs the planning, enactment, and immediate consequences of scorched-earth (bumi hangus) operations in Bengkulu during Indonesia’s Revolutionary War (1945–1949), situating Colonel Barlian’s leadership within the intertwined logics of coercion and protection under severe resource constraints. Using a qualitative, microhistorical case design, we compiled multi-source evidence archival dispatches and administrative minutes, wartime press and photographs, memoirs, local chronicles, and a small set of oral-history interviews screened by provenance and subjected to systematic source criticism. Analysis combined event chronology, inductive coding, and process tracing to link command intent, inter-organizational coordination, engineering practice, and short-term outcomes, with cross-source triangulation and retention of negative cases to test rival explanations. Results indicate that denial measures were calibrated rather than ad hoc: targeted bridge demolitions, controlled destruction of administrative assets, and route obstruction were synchronized with civilian movement to slow mechanized advance, deny administrative utility, and signal non-cooperation; learning effects were evident in the shift from earlier demolition failures to engineer-guided weak-point targeting, and intermediary civic organizations proved crucial for logistics, reception, and communication. We conclude that Bengkulu’s bumi hangus constituted a bounded defensive repertoire embedded in local geography, logistics, and institutional capacity, and that representational scarcity (thin visual archives) has contributed to its underrepresentation relative to Java-centric narratives. Limitations include single-site scope, fragmentary and sometimes propagandistic sources, and the absence of systematic engineering logs despite mitigation via triangulation and weighting by credibility. Implications: decolonization historiography should systematically incorporate defensive signaling and infrastructure denial alongside offensive episodes; archival recovery should prioritize provincial visual/technical records; and future research should extend comparative testing across coastal Sumatra, integrate Dutch–Indonesian technical logs to estimate delay effects, and develop geospatial reconstructions linking demolition sequencing, route interdictions, and civilian protection at scale.